Use of synthetic polymeric fibres - Mumbai Archive Project Team (Jio Institute, 2024)
Until the twentieth century, nets were made from natural fibres obtained from coir, palm leaf, hemp, and grasses. Later, cotton was also used. In the 1950s, natural fibres began to be replaced by synthetic polymeric fibres, which lasted longer, were cheaper and lighter, and allowed for mass production in factories.